Different Anti-Vascular Endothelial Growth Factor for Patients With Diabetic Macular Edema: A Network Meta-Analysis - Wang, Xian; He, Xiaoning; Qi, Fang; Liu, Jia; Wu, Jing (Frontiers in Pharmacology, 2022)
Importance: there are few head-to-head trial data to guide selection of an individual anti-vascular endothelial growth factor (VEGF) inhibitor for diabetic macular edema (DME). Objective: we aimed to assess the efficacy and safety of anti-VEGF for DME and to explore the differences between the relevant options by using network meta-analysis (NMA). Data Sources: we searched MEDLINE, Embase, the Cochrane Library, Web of Science, Chinese Biomedical Literature Database, Wanfang, China National Knowledge Infrastructure, and VIP databases for published randomized controlled trials (RCTs) from their inception to November 2020. Study Selection: we included RCTs of anti-VEGF drugs (intravitreal aflibercept [IVT-AFL], intravitreal ranibizumab [IVR], and intravitreal conbercept [IVC]) used for the treatment of adult patients (≥18 years old and of both sexes) who were diagnosed with DME, regardless of stage or duration of the disease. Data Extraction and Synthesis: we estimated summary odds ratios (ORs) and mean difference (MDs) with 95% credible intervals (CrIs) using a Bayesian NMA. Main Outcomes and Measures: visual outcomes: mean change in BCVA (measure in Early Treatment Diabetic Retinopathy Study [ETDRS] letters) from baseline and the proportion of patients with a gain of at least 15 ETDRS letters. Results: we identified 43 RCTs comprising 8,234 patients. Beneficial effects were observed in patients treated with IVT-AFL compared with those who were treated with other anti-VEGF therapies at 1-year follow-up with regard to improvements in best-corrected visual acuity (BCVA) and the proportion of patients with a gain of at least 15 ETDRS letters . The effect of improvement in BCVA was identified for IVT-AFL compared to intravitreal bevacizumab. At the 2-year follow-up, numerical differences were identified favoring IVT-AFL, however they did not reach statistical significance when comparing IVT-AFL to IVR. In the analysis of adverse events, IVT-AFL showed a lower risk of incidence of ocular adverse events compared to other anti-VEGF therapies at 1-year follow-up. Conclusions and Relevance: IVT-AFL resulted in greater beneficial visual effects and fewer ocular adverse events occurred, compared to IVR or IVC at 1 year after treatment. At 2 years there was insufficient evidence to identify which anti-VEGF has superior efficacy or safety.